Microalgae-bacteria interactions : - Ramli, Norulhuda Mohamed (Wageningen University, 2018)
The roles of algae in improving aquaculture water quality are well-established. However, the integration of algae in a recirculating aquaculture systems (RAS) is less popular mainly due to the large area required for photosynthesis. As science progresses, a growing number of reports are available on the benefits of algae to water quality and fish health. This motivated the author to investigate the effects of algae on a RAS stability, by measuring the water quality and the effects on bacterial community composition in a RAS.